2021
DOI: 10.3390/su14010330
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sustainability and Leadership on the Innovation Management of Michelin-Starred Chefs

Abstract: This study considers relationships among leadership styles and skills (sustainability leadership, innovation leadership and sustainable innovation) as drivers of sustainable innovation capability in the Michelin-starred restaurant context. The study used semi-structured qualitative interviews with a sample of nine chefs in Germany. The purpose was to examine the impact of sustainability and leadership on the innovation management of Michelin-starred chefs and to determine crucial aspects impacting haute cuisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
0
8
0
1
Order By: Relevance
“…First, effective leadership is essential for organizational competitiveness. Mrusek et al [ 47 ] argued that Michelin-starred restaurants with sustainable chefs ensure employee satisfaction, thereby lowering their employee turnover. A study by Abdien [ 48 ], which examined employees of a 5-star hotel chain in Egypt, found that the higher the manager’s support and communication among colleagues as well as between employees and supervisors, the lower the turnover intention.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…First, effective leadership is essential for organizational competitiveness. Mrusek et al [ 47 ] argued that Michelin-starred restaurants with sustainable chefs ensure employee satisfaction, thereby lowering their employee turnover. A study by Abdien [ 48 ], which examined employees of a 5-star hotel chain in Egypt, found that the higher the manager’s support and communication among colleagues as well as between employees and supervisors, the lower the turnover intention.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…From the results, identified sustainable practices are mentioned by less than 50% of M3SRs with the highest percentage being local food (42.96%) and the least percentage being food foraging (5.19%). For research question one, "the extent to which sustainable practices are promoted as part of MSRs' offerings", the results indicate that sustainability has not been considered a necessary offering in M3SRs or a keyword in their website marketing and further reflect M3SRs' failure to embrace sustainability, which is inconsistent with their roles as sustainability ambassadors that previous studies suggest [37,46,89]. This phenomenon has some possible explanations.…”
Section: Resultsmentioning
confidence: 64%
“…However, restaurant entrepreneurs claim they generate new ideas by imitating competitors' promotion practices, insight, and analysis of customer experiences and feedback (C. Lee al., 2019). To this end, the successful implementation of innovations lies in strategic management choices and effective communication among stakeholders, including suppliers and customers (Mrusek et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Transformational leadership has been found to positively influence employee creativity by increasing involvement in generating innovative ideas (Cheung & Wong, 2011). Leadership skills are important for promoting employee creativity, engagement, and long-term success (Mrusek et al, 2022). Thus, innovation seeks to provide differentiated solutions to problems and thus represents a break from previously provided solutions.…”
Section: Introductionmentioning
confidence: 99%